DNA barcoding combined with high-resolution melting analysis to discriminate rhubarb species and its traditional Chinese patent medicines - Shen, Luyi; Zhang, Min; Qiu, Yanmei; Yang, Lin; Lu, Yiwen; Li, Hua; Zhang, Leilei; Tang, Fan; Wang, Feijuan; Zhu, Cheng; Bao, Hexigeduleng; Ding, Yanfei (Frontiers in Pharmacology, 2024)
Rhubarb is a frequently used and beneficial traditional Chinese medicine (TCM).Because wild resources of these plants are constantly being depleted, rhubarb products have been subjected to an unparalleled level of adulteration. Consequentially, reliable technology is urgently required to verify the authenticity of rhubarb raw materials and commercial botanical drugs. In this study, the barcode-DNA high-resolution melting (Bar-HRM) method was applied to characterize 63 rhubarb samples (five Polygonaceae species: Rheum tanguticum, Rh. palmatum, Rh. officinale, Rumex japonicus and Ru. sp.) and distinguish the rhubarb contents of 24 traditional Chinese patent medicine (TCPM) samples. Three markers, namely ITS2, rbcL and psbA-trnH, were tested to assess the candidate DNA barcodes for their effectiveness in distinguishing rhubarb from its adulterants.A segment from ITS2 was selected as the most suitable mini-barcode to identify the botanical drug rhubarb in TCPMs. Then, rhubarbs and TCPM samples were subjected to HRM analysis based on the ITS2 barcode. Among the tested barcoding loci, ITS2 displayed abundant sites of variation and was effective in identifying Polygonaceae species and their botanical origins. HRM analysis based on the ITS2 mini-barcode region successfully distinguished the authenticity of five Polygonaceae species and eight batches of TCPMs. Of the 18 TCPM samples, 66.7 % (12 samples) were identified as containing Rh. tanguticum or Rh. officinale. However, 33.3 % were shown to consist of adulterants. These results demonstrated that DNA barcoding combined with HRM is a specific, suitable and powerful approach for identifying rhubarb species and TCPMs, which is crucial to guaranteeing the security of medicinal plants being traded internationally.